Christmas mice! - Roberts, Bethany; Cushman, Doug (New York : Clarion Books, 2000)
A group of mice have fun as they go about their preparations for Christmas.
1.5
K-3
K-3
AD 170
Keywords: Mice -- Fiction; Christmas -- Fiction; Stories in rhyme; Mice -- Fiction; Christmas -- Fiction; Stories in rhyme